The Golgi-associated COPI-coated buds and vesicles contain β/γ-actin - Valderrama, Ferran (The National Academy of Sciences, 2000)
It has been shown previously that the morphology and subcellular positioning of the Golgi complex is controlled by actin microfilaments. To further characterize the association between actin microfilaments and the Golgi complex, we have used the Clostridium botulinum toxins C2 and C3, which specifically inhibit actin polymerization and cause depolymerization of F-actin in intact cells by the ADP ribosylation of G-actin monomers and the Rho small GTP-binding protein, respectively. Normal rat kidney cells treated with C2 showed that disruption of the actin and the collapse of the Golgi complex occurred concomitantly. However, when cells were treated with C3, the actin disassembly was observed without any change in the organization of the Golgi complex. The absence of the involvement of Rho was further confirmed by the treatment with lysophosphatidic acid or microinjection with the constitutively activated form of RhoA, both of which induced the stress fiber formation without affecting the Golgi complex. Immunogold electron microscopy in normal rat kidney cells revealed that β- and γ-actin isoforms were found in Golgi-associated COPI-coated buds and vesicles. Taken together, the results suggest that the Rho signaling pathway does not directly regulate Golgi-associated actin microfilaments, and that β- and γ-actins might be involved in the formation and/or transport of Golgi-derived vesicular or tubular intermediates.